Learning to Recite the Qur'an Using the Baghdadiyah Method in Early Childhood: A Traditional Dayah Learning Model in Aceh - Karuni Humairah Arta; Sugito Sugito (STAI Hubbulwathan Duri, 2023)
This study aims to describe learning to recite the Qur'an using the Baghdadiyah method as typical Qur’an learning in Aceh, especially in the Traditional Dayah of Aceh. This research belongs to qualitative descriptive. The data were collected through observation, interviews, and documentation. The data were gained by extracting the interview results with the headmaster of Dayah in Aceh Besar, Aceh, conducting observations of the implementation of the Baghdadiyah method, and reviewing the supporting documents. The analysis was data reduction, data presentation, and conclusions. The results showed that learning to recite Al-Qur'an in Aceh Besar employed the Baghdadiyah method during the learning process. The students recite the Qur’an by spelling, followed by Nala (reading without spelling) and fluent Qur’an reciting.